2003
DOI: 10.1046/j.1444-2906.2003.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation among three color variants of Japanese sea cucumber Stichopus japonicus

Abstract: In order to evaluate genetic differentiation among three color variants (red, green and black) of Japanese sea cucumber, Stichopus japonicus, 11 isozyme loci were used as genetic markers for 448 individuals collected from four localities around Japan. Significant differences of allele frequencies were observed between all pairs of color types sympatrically. Average genetic distances at seven loci between the three sympatric color types were 0.0173 between the red and the other color types, and 0.0015 between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
44
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 11 publications
4
44
0
1
Order By: Relevance
“…Nishimura (1995) reported that the red race inhabits gravel beds offshore, while the green and the black races inhabit sand-muddy bottom inshore. Kanno and Kijima (2002) found the red color is discontinuous from the other color races quantitatively (numerical value of the skin color by L*a*b color model) and qualitatively (pigment composition), while the green and black variants show continuous color distribution and the same pigment composition. Microsatellite analysis of the three color variants indicates a separate species status for the red variant and the other color races (Kanno et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Nishimura (1995) reported that the red race inhabits gravel beds offshore, while the green and the black races inhabit sand-muddy bottom inshore. Kanno and Kijima (2002) found the red color is discontinuous from the other color races quantitatively (numerical value of the skin color by L*a*b color model) and qualitatively (pigment composition), while the green and black variants show continuous color distribution and the same pigment composition. Microsatellite analysis of the three color variants indicates a separate species status for the red variant and the other color races (Kanno et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…However, A. japonicus shows continuous color variation among the three color types, and various degrees of intermediate color types occur at different locations [9]. In particular, qualitative difference of color traits between green and black types is unclear [10], because a quantitative boundary between green and black types has not been found in the color-system estimation (RGB and L*a*b system) [10].…”
Section: Introductionmentioning
confidence: 99%
“…population studies of A. japonicus have been generally limited to allozymes (Kanno and Kijima 2003), and microsatellites (Kanno et al 2006). In view of potential limitations of these approaches, we sought to add an additional class of markers, single nucleotide polymorphisms (SNPs), which possess a number of advantages for the study of population structure (Morin et al 2004).…”
mentioning
confidence: 99%